EXTH-48. GALECTIN-1 INHIBITION SENSITIZES RADIATION TREATMENT IN A PRE-CLINICAL MODEL OF GLIOBLASTOMA. (11th November 2019) - Henderson, Fraser; Das, Arabinda; Kanginakudru, Indira; McDonald, Daniel G; Kosnik Infinger, Libby; Vandergrift III, William; Varma, Abhay; Vanek, Kenneth N; Lindhorst, Scott; Patel, Sunil; Cachia, David
Abstract: Radioresistance remains a major clinical challenge in glioblastoma (GB) therapy. However, the mechanism for the development of radioresistance in GB is unclear. Mounting evidence suggests that Galectin-1 (Gal1: a carbohydrate-binding protein galectin-1) contributes to the radioresistance of GB tumors. Recently, several Gal1-targeting compounds have emerged. OTX008 is a calixarene derivative designed to bind the Gal1 amphipathic β-sheet conformation. Our study aimed to reduce galectin-1 expression using OTX008 in a human GB pre-clinical model. For these studies an in vivo GL261 murine models of GB were utilized to assess efficacy of treatment with radiation plus OTX008. Our results demonstrated that inhibition of Gal-1 with OTX008 plus radiation showed significantly decrease in GB growth rate and improved survival in in vivo. OTX008 treatment plus radiation was associated with downregulation of Gal1 and Ki67 in treated tumors, as well as decreased microvessel density and VEGFR2 expression. Finally, combination studies showed OTX008 synergy with radiation therapies, principally when OTX008 was administered first. This study provides insights of Gal-1inhibitory effects of OTX008 and its enhancement of the efficacy of radiotherapy in mouse models of GB suggest that further studies are warranted.